(untitled) (Bulletin KNOB, 2002)
After Besemer’s building-historical research (note 2) in this article an effort has been made to investigate the place of the St Laurens church in the architecture of its time. A comparison with similar projects in the surroundings, for which more data were available in the records, proved to be necessary. In the County Holland the Brabant stone trade had secured the market with an increasingly sizeable supply of hewn material. For the commissioners the choice of the material, the delivery period and obtaining a reasonable price were particularly important. For this purpose a master of the stonework was enlisted as an adviser, who only came over from time to time, on call, sometimes for just one piece of advice, for other works for many years’ guidance from a distance. In Rotterdam the hand of such a master is to be recognised at the points of time when the two large orders of stone were made. The first adviser must have been called in around 1463, when the contracts for the stone of the nave were concluded. It is likely that the Utrecht cathedral architect Jacob van der Borch was charged with this task. A second leader was necessary around 1488, when the large bulk of stonework for the choir and the transepts had to be arranged. By that time the use of stone had increased to such an extent that more stonemasons and advisers were available. It is clear that the major masters, Anthonis Keldermans and Cornelis de Wael were passed over and a local figure was charged with the leadership. The latter concurred with the nave, which resulted in a complete interior, but effected a fascinating and original composition of the choir section. A master of the St John’s church in Gouda may have played this role. At any rate, the St Laurens church originated from a co-operation between the Brabant stone trade and the Dutch masters and their advisers.